2017
DOI: 10.1111/jgs.14855
|View full text |Cite
|
Sign up to set email alerts
|

Real‐World Clinical Characteristics and Treatment Patterns of Individuals Aged 80 and Older with Nonvalvular Atrial Fibrillation: Results from the ReAl‐life Multicenter Survey Evaluating Stroke Study

Abstract: Nearly one-fifth of individuals with NVAF in this real-world sample were aged 80 and older. Participants aged 80 and older were more likely to be female and have more comorbidities than those who were younger than 80. Those aged 80 and older with AF were less likely to receive anticoagulants than those who were younger than 80, but having more comorbidities and other individual-level characteristics may explain this difference. When they were prescribed OACs, participants aged 80 and older had poorer quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
(57 reference statements)
1
10
1
Order By: Relevance
“…4,14,23,24 However, survey data showed that AF patients, aged ≥80 years are more likely to receive antiplatelet medication than younger patients. 25 In the present data, only approximately one-quarter of patients diagnosed with AF received OAC before death, and centenarians with AF received significantly less anticoagulant therapy than younger age groups. Nevertheless, the rate of anticoagulation therapy increased over the study period in all age groups, which might be explained by the introduction of NOACs onto the market and with rates of comorbidities.…”
Section: Discussioncontrasting
confidence: 42%
“…4,14,23,24 However, survey data showed that AF patients, aged ≥80 years are more likely to receive antiplatelet medication than younger patients. 25 In the present data, only approximately one-quarter of patients diagnosed with AF received OAC before death, and centenarians with AF received significantly less anticoagulant therapy than younger age groups. Nevertheless, the rate of anticoagulation therapy increased over the study period in all age groups, which might be explained by the introduction of NOACs onto the market and with rates of comorbidities.…”
Section: Discussioncontrasting
confidence: 42%
“…Several patient characteristics are associated with lower rates of OAC prescribing including older age, female sex, antiplatelet use, and comorbid conditions . Beyond these clinical factors, providers frequently cite actual or perceived fall risk and age‐related impairments as reasons for AC withholding .…”
mentioning
confidence: 99%
“…7,8 Several patient characteristics are associated with lower rates of OAC prescribing including older age, female sex, antiplatelet use, and comorbid conditions. [9][10][11] Beyond these clinical factors, providers frequently cite actual or perceived fall risk and age-related impairments as reasons for AC withholding. 12,13 Studies have shown that physician perceptions of stroke and bleeding risk in patients with AF do not consistently relate to validated risk score estimations.…”
mentioning
confidence: 99%
“…Frailty, chronic renal disease and polypharmacy are the main contributors of elevated embolic and bleeding risk in these patients that have to be taken into consideration when making a decision on OAC therapy 11 . We showed that physicians tend to prescribe more OAC for elderly NVAF patients if they had elevated risk score for stroke and lower risk score for bleeding 10 . However, currently available risk scores are far from perfect.…”
Section: Switching Among Oral Anticoagulants: Is It Logical?mentioning
confidence: 87%
“…Elderly patients have an increased risk for stroke, however, OACs were generally less prescribed to these patients because of comorbidities 10 . Frailty, chronic renal disease and polypharmacy are the main contributors of elevated embolic and bleeding risk in these patients that have to be taken into consideration when making a decision on OAC therapy 11 .…”
Section: Switching Among Oral Anticoagulants: Is It Logical?mentioning
confidence: 99%